PERAN MAHKAMAH AGUNG DALAM MENJAGA KONSISTENSI PUTUSAN PERKARA SYARIAH - Jauhari, Muhammad Sofwan (An Nawawi, 2024)
Religious justice in Indonesia has developed since the reform era with the establishment of the Supreme Court (MA) of the Republic of Indonesia in the field of Religious Justice in 2003. However, the consistency of sharia rulings is still a concern due to differences in the interpretation of Islamic law, cultural diversity, the quality of judges, and limited resources. This study uses normative legal methods to identify factors that cause inconsistencies in decisions, analyze the role of the Supreme Court, and formulate recommendations. The results show that the inconsistency of the decision is influenced by legal and non-legal factors. To overcome this, it is necessary to improve the quality of judges, develop technical guidelines, and improve coordination between religious judicial institutions. The Supreme Court plays an important role in maintaining the consistency of sharia case decisions with judge guidance, technical guidelines, coordination, and cooperation with related institutions. Hopefully this research can help improve the quality of religious justice in Indonesia through the Supreme Court.